Risky Sexual Behaviors as Correlates of Depression and Suicidal Ideation Among Male HIV Test-Seekers at a Voluntary Counseling and Testing Facility in Taiwan. (April 2017) - Lin, Chia-Chun; Lee, Yuan-Ti; Yang, Hao-Jan
This study aims at determining the level of depression and suicidal status of adult HIV test-seekers. Of the total enrolled 850 males, almost 50% reported some risk behaviors, 38.9% experienced depression, and 7.2% had suicidal ideation. Subjects with risky sexual behaviors in terms of repeated HIV test, had a history of sexually transmitted disease, engaged in one-night stands, or did not use condoms all the time with causal sexual partners were more likely to have depression. Furthermore, subjects who were bisexual/homosexual, engaged in Internet sex, engaged in one-night stands, or used addictive drugs within the past 6 months were more likely to experience suicidal ideation. The HIV testers are at risk of experiencing depression and suicidal ideation; each is associated with different types of risky sexual behaviors. It is essential for the health authority to further provide mental health services for HIV testers and to draw up an effective strategy in reducing unprotected sexual behaviors.